Adoption and implementation of IT governance: cases from Australian higher education - Bhattacharjya, J.; Chang, Vanessa (Information Science Reference, 2008)
This chapter introduces key IT governance concepts and industry standards and explores their adoption and implementation in the higher education environment. It shows that IT governance processes, structures and relational mechanisms adopted by these institutions generate value through improvements in a number of key focus areas for IT management. It is hoped that the study will inform both practitioners and researchers and lead to a better understanding of the relationship between IT governance structures, processes and relational mechanisms and business benefits.